Pengaruh Minat Belajar Anak terhadap Kemampuan Menghafal Surah Pendek di Desa Deli Tua - Atika Dhini Insani Nasution; Juli Julaiha; Annisa Salsabila; Putri Zulaykha; Nurhariyana Nurhariyana; Nabila Nabila; Nilsya Rezeky Aprilia Dhalimunthe; Nuratina Nuratina; Puspita Rima Melati Harahap; Dilia Meylandri Sirait1; Diah Juliani (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
This article discusses the effect of children's interest in learning on the ability to memorize short surahs in Deli Tua Village. The purpose of this article is to describe the effect of children's interest in learning on the ability to memorize short surahs in Deli Tua Village. The research used is Ex-post facto research. The sample of this study amounted to 20 early childhood children in Deli Tua Village. The research instruments used were observation sheets and analytical techniques using classical assumption test statistics for normality and linearity formulas, as well as experimental research tests for product moment formulas and correlations. The results of this study are that children's interest in learning has an influence on the ability to memorize short surahs. Keywords: Learnig style, Multiple Intelligences, Early Childhood